A obrigatoriedade de aplicação do artigo 489, parágrafo 1º, do CPC ao processo do trabalho - Portela, Vinícius José Rockenbach (2017)
With the advent of the new Code of Civil Procedure (Law no. 13.105/2015), it emerged the obligation of analytical reasoning in judgments, laid down in article 489, paragraph 1, of the CPC, which sets forth the hypothesis in which will be not considered, for all legal purposes, reasoned the judgments. It turns out that part of the doctrine and the jurisprudence opposed barriers to the application of the referred legal dispositive to the procedural labor law, for they understand that it would not be fulfilled the requirements set out in article 769 of the CLT. In other words, under the arguments that there is no gap in the labor process ordinance and that the analytical reasoning would be incompatible with the procedural labor law. On the other hand, the other part of the doctrine and jurisprudence holds that the analytical reasoning is an important legal mechanism in combating judicial activism present in the labor courts, supporting the completion of the requirements set out in the law for implementation of common standards in labor process. Therefore, the doctrinal and jurisprudential debate, it abides to this work to address scientifically the question inherent in the requirement of analytical reasoning of judicial decisions in the labor process, mainly aiming to submit a proposal of a solution to this problem. After long research stabilized in doctrine and jurisprudence, it reaches two main conclusions. The first is that the article 489 of the CPC is not incompatible with the systematic and principiology of the procedural labor law, which is, therefore, perfectly applicable supplementarily to the labor process, before the existence of partial regulatory gap in CLT. Finally, the second conclusion is that it is essential that they are committed to efforts for the creation of a Code of Labor Procedure that contains sufficient mechanisms for the solution of the problems that plague labor relations in the present days, because, only that way, the labor process will return to have its vanguard status of a rapid, simple and effective process model, pursued by other procedural systems.